Interaction Effects of Stride Angle and Strike Pattern on Running Economy - Santos-Concejero, J.; Tam, N.; Granados, C.; Irazusta, J.; Bidaurrazaga-Letona, I.; Zabala-Lili, J.; Gil, S. M. (International Journal of Sports Medicine, 2014)
This study aimed to investigate the relationship between stride angle and running economy (RE) in athletes with different foot strike patterns. 30 male runners completed 4 min running stages on a treadmill at different velocities. During the test, biomechanical variables such as stride angle, swing time, contact time, stride length and frequency were recorded using an optical measurement system. Their foot strike pattern was determined, and VO2 at velocities below the lactate threshold were measured to calculate RE. Midfoot/forefoot strikers had better RE than rearfoot strikers (201.5±5.6 ml · kg−1 · km−1 vs. 213.5±4.2 ml · kg−1 · km−1respectively; p=0.019). Additionally, midfoot/forefoot strikers presented higher stride angles than rearfoot strikers (p=0.043). Linear modelling analysis showed that stride angle is closely related to RE (r=0.62, p<0.001) and that the effect of stride angle on RE was different in the 2 groups. From an arbitrary value of 4°, a rearfoot strike pattern is likely to be more economical, whereas at any lower degree, the midfoot/forefoot strike pattern appears to be more desirable. A biomechanical running technique characterised by high stride angles and a midfoot/forefoot strike pattern is advantageous for a better RE. Athletes may find stride angle useful for improving RE.
Keywords: biomechanics; ground contact; performance; correlation; rearfoot; midfoot/forefoot